1994
DOI: 10.1037/0022-0167.41.2.162
|View full text |Cite
|
Sign up to set email alerts
|

How multiculturalism obscures racial factors in the therapy process: Comment on Ridley et al. (1994), Sodowsky et al. (1994), Ottavi et al. (1994), and Thompson et al. (1994).

Abstract: Janet E. HelmsThis article argues that counseling psychologists have prematurely abandoned the study of racial factors in the psychotherapy process in favor of an all-inclusive version of multiculturalism. Using 4 multicultural articles (T. M.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…Moreover, although existing self-report multicultural counseling competence scales are claiming to measure respondents' ability to work with a range of cultural (e.g., racial, ethnic, gender, social class, and sexual orientation) groups, a review of the instruments' items suggests that perceived ability to work effectively with people of color seems to be the primary construct measured. As Helms (1994)cogently asserted, multiculturalism and analogous terms may be useless as scientific constructs because they lack specificity with regard to identifying aspects of individual diversity. Furthermore, she suggested that when categorizing certain behaviors as “cultural,” the specific dimensions presumed to be cultural should be identified and assessed (or a means proposed for assessment).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, although existing self-report multicultural counseling competence scales are claiming to measure respondents' ability to work with a range of cultural (e.g., racial, ethnic, gender, social class, and sexual orientation) groups, a review of the instruments' items suggests that perceived ability to work effectively with people of color seems to be the primary construct measured. As Helms (1994)cogently asserted, multiculturalism and analogous terms may be useless as scientific constructs because they lack specificity with regard to identifying aspects of individual diversity. Furthermore, she suggested that when categorizing certain behaviors as “cultural,” the specific dimensions presumed to be cultural should be identified and assessed (or a means proposed for assessment).…”
Section: Discussionmentioning
confidence: 99%
“…Helms and Cook (1999) have observed that mental health professionals often adopt very broad definitions that view “virtually all aspects of human diversity as equivalent” (p. 29). Sue et al (1998) have argued that definitions can become so broad that they are rendered meaningless, and Helms (1994) has argued that race is often obscured by broad definitions of multiculturalism, which allow mental health professionals to ignore their own racial biases. These issues must be considered as they apply to a particular organization and the populations they serve.…”
Section: Training Philosophymentioning
confidence: 99%
“…Admittedly, it is impractical to expect that a single document could address all the nuances associated with every aspect of diversity. Indeed, Helms (1994) has commented on the limitations of using the term multiculturalism without specifying a variable of interest. Thus, competency for a given cultural characteristic is best described by guidelines specific to that aspect of diversity (Constantine, Gloria, & Ladany, 2002).…”
mentioning
confidence: 99%